Power of the Pen or the Gavel? Determining Asylum Standards on the Courts of Appeals. (3rd July 2019) - Stobb, Maureen
Abstract: The judiciary is subject to constraint from Congress through numerous mechanisms. In particular, Congress can limit judicial discretion through the content of the statutes it passes. After the September 11 attacks, Congress sought to constrain judicial behavior through the REAL ID Act (2005). In response to growing fear of fraud in the asylum process, Congress instructed federal judges reviewing administrative decisions to consider minor inconsistencies in an applicant's testimony as undermining his or her credibility, a crucial component of a refugee's claim. Despite Congress's clear abrogation of the prior rule in these cases, some federal appellate courts have refused to let go of their pre–REAL ID standard. In this article, I investigate the factors explaining when judges on the U.S. Courts of Appeals will defy the express language of a congressional statute in exercising their power of review in asylum cases. The results indicate that congressional directives are not, alone, enough to compel judges to adopt a legal standard. I find that circuit-level legal and policy factors are the strongest predictors of whether a federal court of appeals judge will try to limit the standard designated by Congress. At the same time, evidence suggests that judges consider the risk of a congressional override. My findings not only add to our understanding of legislative–judicial interactions, but also contribute to the growing movement to understand the politics of legal doctrine.